Penggunaan Metode Quantum Teaching dalam Pembelajaran PAI di Kelas V SD Inpres Atu`Laleng, Kecamatan Buyasuri, Kabupaten Lembata, Provinsi Nusa Tenggara Timur - Gozali, Marwan; Amirullah (Prodi Pendidikan Agama Islam, 2022)
From the steps of implementing learning, namely starting from the introduction, core and closing activities carried out by PAI teachers. This research uses qualitative research with qualitative descriptive research type. The collection technique is observation, interview, and documentation. Data analysis techniques are data reduction, data presentation, and drawing conclusions. As a test of the validity of the data, namely by extending the presence of researchers and triangulation. The results of this study can be seen from the enthusiasm and enthusiasm of students in participating in learning and the results are very good and cooperation between teachers and students and students and students, students dare to have opinions and students can respect other opinions.